1991
DOI: 10.2172/10189843
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic and trace element characteristics of rhyolites from the Valles Caldera, New Mexico. Final technical report

Abstract: This report was prepared as an account of work sponsored by an agency of the United St'ates _ _ ]'_ _ _' _ _e_ Government. Neither the United States Government nor any agency thereof, nor any of their _ _ _ [[ employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights.Refer. ence herein to any sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The LBT consists almost entirely of high-silica rhyolite of constant major element composition with pronounced variations in minor and trace elements (Table V2), accom panied by phenocryst contents from 7.5 to 19.5% (Self et al, 1991). In proximal sections, these variations are systematic from first-erupted to last-erupted units, and closely mimic element zoning patterns seen in the Bishop Tuff (Hildreth, 1979) and other high-silica rhyolites (Fig.…”
Section: Geochemistry Of the Bandelier Tuffmentioning
confidence: 52%
See 4 more Smart Citations
“…The LBT consists almost entirely of high-silica rhyolite of constant major element composition with pronounced variations in minor and trace elements (Table V2), accom panied by phenocryst contents from 7.5 to 19.5% (Self et al, 1991). In proximal sections, these variations are systematic from first-erupted to last-erupted units, and closely mimic element zoning patterns seen in the Bishop Tuff (Hildreth, 1979) and other high-silica rhyolites (Fig.…”
Section: Geochemistry Of the Bandelier Tuffmentioning
confidence: 52%
“…Determination of the age of these units has proved difficult; the published 40 Ar/ 39 Ar ages on the El Cajete, Battleship Rock, and Banco Bonito units range from 0.5 to 0.2 Ma (Spell and Harrison, 1993). Self et al (1991) suggest that an eruption at about 300 ka produced the El Cajete-Battleship Rock-VC1 rhyolite units, and that a slightly later eruption at about 200-150 ka yielded the Banco Bonito lava and associated pyroclastic rocks. This scenario is supported by 40 Ar/ 39 Ar ages of Spell and Harrison (1993), see Table V1, but a new study has suggested an age of about 60 ka for these units (Wolff and Gardner, 1995).…”
Section: Valles Rhyolites and Associated Depositsmentioning
confidence: 92%
See 3 more Smart Citations